Improving childcare staff management of acute asthma exacerbation – An Australian pilot study. (9th August 2017) - Soo, Yien Yien; Luckie, Kate Helen; Saini, Bandana; Kritikos, Vicky; Brannan, John D.; Moles, Rebekah Jane
ABSTRACT: Objective: This study aimed to evaluate the effectiveness of an asthma first-aid training tool for childcare staff in Australia. The effects of training on both asthma knowledge and skills were assessed. Methods: A pre/post-study design was utilised to assess changes in asthma knowledge and asthma first-aid skills in childcare staff before and after an educational intervention. Asthma first-aid skills were assessed from the participant's response to two scenarios in which a child was having a severe exacerbation of asthma. Asthma knowledge and asthma skills scores were collected at base-line and 3 weeks post the education session, which involved feedback on each individual's skills and a brief lecture on asthma delivered via PowerPoint presentation. Results: There was a significant improvement after intervention in asthma knowledge (Z = −3.638, p < 0.001) and asthma first-aid skills for both scenario 1 (Z = −6.012, p < 0.001) and scenario 2 (Z = −6.018, p < 0.001). In scenario 1 and 2, first-aid skills improved by 65% ( p < 0.001) and 57% ( p < 0.001), respectively. Asthma knowledge was high at baseline (79%) and increased by 7% ( p < 0.001) after the educational intervention. These asthma knowledge results were not significant when adjusted for prior knowledge. Results suggest that knowledge assessment alone may not predict the practical skills needed for asthma first-aid. Conclusions: Skills assessment is a useful adjunct to knowledge assessment when gauging the ability of childcare staff to manage acute asthma exacerbation. Skills assessment could be considered for incorporation into future educational interventions to improve management of acute asthma exacerbation.